THE MAIN FUNCTIONS AND PRACTICAL IMPORTANCE OF RADIO TELESCOPES - Navro‘za, Primova (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This The article not only provides information about radio telescopes, their constituent parts and the principle of operation, but also gives a brief overview of the role of radio telescopes in our lives and the radio telescopes that have grown not only in Uzbekistan, but also in many other countries.